Low-carbon development of the municipal solid waste management industry - Ivanova Anna; Lopatin Victor (BIO Web of Conferences)
The current system of municipal solid waste management causes environmental problems such as air, water and land pollution, the possibility of fires, which leads to public health problems. In this case, the quality of clean steam gases was tested during waste management. The analysis of outcome management technologies shows the most promising projects leading to a reduction in greenhouse gas emissions, which can be implemented as climate projects and, thus, attract more investment in the development of the industry. An assessment was made of the possibilities of implementing projects in the field of waste management aimed at reducing greenhouse gas in the Voronezh Region.